The Creativity of Elementary School Science Teachers in Implementing Project-Based Learning: A Case Study - Fitri April Yanti; Rendy Wikrama Wardana (Universitas Nahdlatul Ulama Surabaya, 2024)
The ability to implement learning models in the classroom is a pedagogic competence for teachers. However, in preparing, implementing, and evaluating project-based learning, teacher creativity is needed. Creativity is the result of a creative thinking process. The purpose of this study was to explore teacher creativity in implementing project-based learning models. It involved 6 elementary school teachers. Teachers were selected by purposive sampling. Data collection is done by observation, interviews, and documentation. Analysis was performed by data reduction, explanation, comparison, and conclusion. Data credibility was tested through data triangulation, peer discussions, and member checks. The results show that teacher creativity in terms of choosing learning methods and media, fostering student learning enthusiasm, applying problem-solving techniques, and compiling project assessments, is better when implementing project-based learning compared to conventional learning. This research is important to develop the creativity of future teachers in teaching